High Capacity and Rate Capability Binder-less Ternary Transition Metal-organic Framework as Anode Material for Lithium-ion Battery - Nurul Khairiyyah, Mohd Zain; Chelladurai, Karuppiah; Izan Izwan, Misnon; Das, Santanu; Ikechukwu Ozoemena, Kenneth; Yang, Chun-Chen; Rajan, Jose (WILEY-VCH Verlag, 2021)
A novel metal-organic framework (MOF) composition containing three cations (CoCuNi MOF) grown directly on nickel foam substrate has been evaluated for its use as an anode material for lithium ion batteries (LIB) and benchmarked the performance with its single cation MOF ounterparts. Equimolar concen-trations of cobalt, copper, and nickel and 1,4-benzenedi-carboxylic acid are used as metal centers and organic linker, eespectively, for synthesis of CoCuNi MOF. The morphology, chemical structure, and electrochemical properties of the materials are studied and analyzed for their suitability for lithium ion storage. The cyclability performance of CoCuNi MOF exhibit good behavior with retaining ~490 (-3) and ~396 (-3) mA·h·g 1 at ~200 and ~500 mA·g 1, respectively. During rate capa-bility evaluation, CoCuNi MOF proved to be the best material compared to its single component MOF:CoCuNi MOF retained an average capacity of ~565 (-3) mA·h·g 1 at current density as high as 1000 mA·g 1 . The positive attributes of CoCuNi MOF are shown to arise from the synergistic effect of the three transition metals. The output from this work is expected to provide useful insight into the design of new MOFs electrode for LIBs with high specific capacity and improved cycle stability.